2010
DOI: 10.1111/j.1463-1326.2010.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pioglitazone on endothelial function in impaired glucose tolerance

Abstract: Pioglitazone improved endothelial function in IGT. Treatment with pioglitazone may reduce the risk of cardiovascular disease in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
(47 reference statements)
2
17
0
Order By: Relevance
“…The results indicated that, in patients with impaired glucose tolerance, pioglitazone may stimulate adiponectin secretion, improve endothelial function and hence inhibit the progression of coronary atherosclerosis. The present study was in accordance with several other investigations [17,18]. Adiponectin, an adipocyte-derived peptide, has important roles in increasing the availability of nitric oxide, reducing oxidative stress and ⁄ or directly enhancing relaxation of vascular smooth muscle, as well as anti-inflammatory actions [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results indicated that, in patients with impaired glucose tolerance, pioglitazone may stimulate adiponectin secretion, improve endothelial function and hence inhibit the progression of coronary atherosclerosis. The present study was in accordance with several other investigations [17,18]. Adiponectin, an adipocyte-derived peptide, has important roles in increasing the availability of nitric oxide, reducing oxidative stress and ⁄ or directly enhancing relaxation of vascular smooth muscle, as well as anti-inflammatory actions [19].…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study indicated that increasing serum adiponectin level might contribute to the effects of pioglitazone in improving endothelial function. With respect to whether improving endothelial function has a role in the mechanism of the beneficial effects of pioglitazone on atherosclerosis, consistent results were reported by different groups [17,18]. The present study also indicated that pioglitazone could increase adponectin secretion, which was correlated with improvement in endothelial function and regression of coronary plaques.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have demonstrated that pioglitazone treatment improves plaque stability and endothelial function [5]–[7] in IGT patients, suggesting that its beneficial effects may also occur in pre-diabetic conditions. Experiments conducted in cultured EPCs supported a positive action of pioglitazone on key regulators of atherosclerosis independently of its metabolic action [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired glucose tolerance (IGT) is a prediabetic condition characterized by insulin-resistance, predisposing to increased cardiovascular disease (CVD) risk [3]. Recent studies have demonstrated that pioglitazone reduces atherosclerotic plaque inflammation [4] and development [5], [6], and improves endothelial function [7] in subjects with IGT, pointing towards potential beneficial CV properties in pre-diabetic conditions. Experimental studies support the hypothesis that putative pioglitazone CV protective effects extend beyond its metabolic action [8], [9], although the precise molecular mechanisms remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that insulin resistance is associated with short-term, but not long-term, attenuation of vascular endothelial function both after test meal ingestion and after oral glucose loading. Oral antidiabetic agents, such as pioglitazone, that decrease insulin resistance also improve endothelial function in patients with diabetes [22] or impaired glucose tolerance [23]. Improvement of fasting FMD is correlated with improvement of insulin resistance [24].…”
Section: Discussionmentioning
confidence: 99%